2020
DOI: 10.1016/j.ijid.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of patients with COVID-19

Abstract: Highlights Nutrients play a vital role in the defense against infectious diseases and the regulation of inflammation; however, little is known with regards to COVID-19. We measured concentrations of vitamins B1, B6, B12, folate, vitamin D (25-hydroxyvitamin D), selenium, and zinc in 50 patients with COVID-19; vitamin D deficiency was shown in 76% of patients and 42% of selenium. It showed a significant difference with 43.3% vit D deficiency of the control groups (150 people)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
219
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(250 citation statements)
references
References 26 publications
16
219
1
14
Order By: Relevance
“…In Table 1B , we report findings from 21 studies in which 25(OH)D levels were measured in individuals hospitalized for COVID-19 or after confirmed positive test for SARS-CoV-2 (via PCR) ( Table 1B ). Eleven of these studies reported significantly lower 25(OH)D levels for those with COVID-19 or who were positive for SARS-CoV-2 infection compared to control groups ( 204 , 205 , 207 – 209 , 211 , 212 , 214 , 218 , 219 , 223 ). Many of these studies were limited by their small sample size, a lack of clarity on what assay was used to measure 25(OH)D, and that 25(OH)D levels were not measured before infection was diagnosed.…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…In Table 1B , we report findings from 21 studies in which 25(OH)D levels were measured in individuals hospitalized for COVID-19 or after confirmed positive test for SARS-CoV-2 (via PCR) ( Table 1B ). Eleven of these studies reported significantly lower 25(OH)D levels for those with COVID-19 or who were positive for SARS-CoV-2 infection compared to control groups ( 204 , 205 , 207 – 209 , 211 , 212 , 214 , 218 , 219 , 223 ). Many of these studies were limited by their small sample size, a lack of clarity on what assay was used to measure 25(OH)D, and that 25(OH)D levels were not measured before infection was diagnosed.…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…The relation of selenium with the immune system is further corroborated in hospitalized patients with COVID-19, in which selenium levels were found sub-optimal [64]. Moreover, good selenium status, as assessed by the selenium hair content, has been connected to a higher recovery rate from COVID-19 [91].…”
Section: Seleniummentioning
confidence: 70%
“…An inverse association between mean levels of vitamin D and the number of COVID-19 cases/1 M was recently reported in a cross-sectional European study whereas a UK study did not find an association between the vitamin's status and COVID-19 risk [62]. Moreover, low levels of vitamin D were found in COVID-19 positive patients [63] or hospitalized patients with COVID-19 [64] and have been connected to the severity of the disease [65][66][67].The hypothesis that vitamin D may explain susceptibility to COVID-19 infection in dark colored skin individuals do not seem to be valid [62]. It is noteworthy that several clinical trials are on the way regarding the role of vitamin D in prevention and treatment of COVID-19, reviewed elsewhere [48].…”
Section: Vitamin Dmentioning
confidence: 86%
“…Food loss and agroindustrial byproducts represent a continuously growing global issue, posing a challenge to food safety and security and negatively impacting the economy and environmental stability. According to FAO, approximately one-third of the The response of human cellular immunity mechanisms to the SARS-CoV-2 viral infection is strongly influenced by host nutrition, mainly by the presence or absence of specific micronutrients and bioactive molecules [14,[35][36][37][38]. An indirect approach is to use different mechanisms that sustain the absorption and bioavailability of bioactive molecules.…”
Section: Bioeconomy Concept Importance In Pandemicmentioning
confidence: 99%